Evaluating the effects of improving forest road standards on economic value of forest products - Akay, Abdullah Emin (Array, 2021)
Forest roads are the key infrastructures that provide access to forest areas for sustainable management, protection, and utilization of forest resources. In order to benefit from the important functions of forest roads, they should be built in with adequate technical road standards. The road network with low technical standards require more frequent major repairs to ensure continues access to forest resources. In addition, only small trucks with low load capacity can move on the low standard roads. Furthermore, the low road standards limit the truck speed that increases vehicle travel time. These negative effects increase the transportation costs which are an important part of the timber production costs in Turkey. Thus, improving the road standards and developing forest transportation planning should be evaluated together in the most appropriate way. Large logging trucks with high load capacity are generally preferred for efficient transportation of wood-based forest products. In Turkey, large logging trucks, however, cannot operate on the most of the forest roads because insufficient technical road standards (road width, curve radius, surface materials, road structures) limit the maneuverability of large logging trucks. In this study, the objective is to determine the effects of improving forest road standards on total net profit of forest products by using the NETWORK 2000 program, a heuristic approach for solving forest transportation problems. Three Forest Enterprise Chiefs (FECs) located in Mustafakemalpaşa Forest Enterprise Directorate (FED) in Bursa Forest Regional Directorate were selected as the study area. The digital data layers for forest road network was generated by using ArcGIS 10.4 software. In the solution process, firstly, the optimum routes that minimize the transportation cost and maximize the total net profit of forest products on existing forest road networks were investigated for a truck type (15 ton) currently used in the region.